Is masonry a religión? - Mola, Aldo Alessando (2023)
When answering the question of whether freemasonry is a religion or not, one needs only to clarify the origins, nature, and purpose of Freemasonry and that of the Catholic Church. It is, evidently, an impossible task to achieve here. Since we cannot avoid approaching the topic, so we can only offer some guidelines for discussion in an attempt to answer these questions.